Undang-Undang Simbur Cahaya dan Piagam Dalam Kebijakan Pencegahan Korupsi Serta Kasus Gratifikasi dan Penyuapan di Kesultanan Palembang - Rahyu Zami; Muhammad Ilham (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
This discussion is about local law that applies in its application, regarding the corruption prevention system written in the charter and the Simbur Cahaya Law issued by the sultan of Palembang. The Simbur Cahaya Law is a very productive law in preventing corruption in remote areas, regional officials are given the authority to carry out legal settlements without the approval of the Palembang sultan so that the fine imposed on the suspect will be divided between the victim and officials in the interior. in solving cases that occurred in their village. After that, it was also discussed about the system of sultanate administration (government) in the hinterland which also carried out the law by giving it to government officials who represented the sultan in the interior and also disseminated to all regions in South Sumatra except the Besemah area because they have their own laws, the charter is also a legal rules that give authority to high-ranking officials in the area that are used to complement the laws that apply in the Besemah area. Gratification was used as a form of giving by local rulers to equal or higher rulers and this was also true in the Palembang Sultanate and one of the bribery cases at the end of the sultanate. The method used in this research is descriptive method, which is the method used to find the elements, characteristics, properties of a phenomenon. This method begins with collecting data, analyzing the data, and interpreting it. The problem that arises is what is the content of laws and charters that contain elements of preventing corruption? and what are the forms of gratification and bribery in the Palembang Sultanate as well as corruption within the VOC itself